JURNALISME ADVOKASI DENGAN METODE JURNALISME CROWDSOURCING DAL AM BERITA KOLABORASI MEDIA DEDUKTIF DAN TIRTO - Ami Fatimatuz Zahro; Febria Adha Larasati (Program Studi Ilmu Komunikasi Universitas Islam Majapahit, 2024)
This research aims to gain an in-depth understanding of how crowdsourcing can be used in investigative journalism practices by the Deductive News Media. It is important to answer the question why and how crowdsourcing may be utilized in investigatory journalistic practices. Research theory is based on the paradigm of qualitative research using case study methods. As for the subject of the research, it is a Deductive Reporter, while the object of its research is an in depth coverage related to reports about the challenges and threats faced by the Student Press Institute (LPM) in Indonesia during 2015-2022 entitled